Pushing the boundaries of hands-on optics experiments with interactive digital simulation - Vincent Casamayou; Bruno Bousquet; Justin Dillmann; Nathan Salin; Jean-Paul Guillet; Lionel Canioni; Martin Hachet (Discover Education)
Abstract Practical work in optics is essential to understand complex abstract phenomena. Consequently, hands-on experiments are part of most physics’ curricula, despite the fact that they can be hard to set up and maintain. In this article, we present a virtual laboratory tool, called SHIRE, which allows students to carry out optical experiments from a desktop computer. SHIRE’s optic simulation is self-adaptive so that it allows the user to set up any optical assembly from scratch. The software includes pedagogical contents that facilitates autonomous work, and it also allows synchronous and asynchronous collaborative work. After a description of how this tool works, we present some examples of use as well as the opinions of the first users. We believe that this new digital tool can help transform current teaching practices in the teaching/learning of optics.